Stress-strain behavior and residual strength of Petobo sand with variable fines content under consolidated undrained triaxial loading - Vidayanti, Desiana; Rahardjo, Paulus Pramono; Nazir, Ramli (SINERGI, 2026)
Liquefaction was one of the primary causes of severe ground deformation during the 2018 Palu earthquake, particularly in the Petobo area, where large-scale flow liquefaction resulted in extensive ground displacement. Despite extensive field investigations, laboratory-based residual shear strength data for Petobo soil had not been available to explain the exceptional mobility of the flowslide. This study investigated the stress-strain response and post-liquefaction residual strength of Petobo silty sand with variable fines content using monotonic consolidated undrained (CU) triaxial tests. Reconstituted specimens were prepared using the moist tamping method with fines contents of approximately 9% and 26.4% and tested under three levels of initial mean effective stress. The results showed that specimens with higher fines content generated excess pore water pressure more rapidly and exhibited stronger contractive behavior at small strains. At large strains, however, both fines contents mobilized comparable residual strength levels, expressed as normalized residual strength ratios (qres/p’0) ranging from 0.79 to 0.94. These findings indicate that while fines content influenced early-stage contractive behavior and pore-pressure generation, its effect on post-liquefaction residual strength under very loose density conditions was limited. The residual shear resistance was primarily governed by the loose sand fabric and the effective stress level at the stabilized post-peak condition. This study provides the first laboratory-based residual shear strength data for Petobo silty sand, offering essential parameters for back-analysis, numerical modeling, and liquefaction hazard assessment related to flow-type deformation in Palu and similar alluvial environments.